2006
DOI: 10.1007/s10368-006-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural breaks and the twin deficits hypothesis

Abstract: Current account adjustment, Public budget deficit, Structural change, Econometric model, Twin deficits, C53, F32, H62,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 33 publications
0
27
1
5
Order By: Relevance
“…Over the past three decades, the twin deficits hypothesis (TDH) -that budget deficit has a direct effect on current account deficit -has been a topic of interest in the empirical literature (see, for example, BahmaniOskooee, 1995; Khalid & Guan, 1999;Mohammadi, 2004;Bagnai, 2006;Salvatore, 2006;Bartolini & Lahiri, 2006;Baharumshah & Lau, 2007;Ito, 2009;Daly & Siddiki, 2009). The causal link between public budget deficit and current account balance has been analyzed extensively in the recent literature, largely because of its implications for long-term economic progress.…”
Section: Introductionmentioning
confidence: 98%
“…Over the past three decades, the twin deficits hypothesis (TDH) -that budget deficit has a direct effect on current account deficit -has been a topic of interest in the empirical literature (see, for example, BahmaniOskooee, 1995; Khalid & Guan, 1999;Mohammadi, 2004;Bagnai, 2006;Salvatore, 2006;Bartolini & Lahiri, 2006;Baharumshah & Lau, 2007;Ito, 2009;Daly & Siddiki, 2009). The causal link between public budget deficit and current account balance has been analyzed extensively in the recent literature, largely because of its implications for long-term economic progress.…”
Section: Introductionmentioning
confidence: 98%
“…Following Engle and Granger they used a three step procedure to test for the direction of the causality. Bagnai (2006) used time series data to evaluate the impact of structural breaks on the long-run and short-run relation between current account, government, and investments in 22 OECD countries. The author found that when allowing for possible existence of structural break, the data reveal more clearly a long-run relation between the current account and the variable controls.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bagnai, 2006;Grier and Ye, 2009). Bagnai (2006) analyses the impact of the change in the government budget balance on the current account in 22 OECD member countries including Turkey using the annual data for the period. Linear estimates support the twin deficits for Denmark, Germany, Italy, Spain, Sweden, Switzerland and Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…However, VAR analysis supports the validity of the twin deficits in the short run. The studies on twin deficits hypothesis for Turkey except for Bagnai (2006) and Catik et al (2015) have utilized linear models and their results vary across the methodology and estimation sample similar to other countries.…”
Section: Introductionmentioning
confidence: 99%